Effect of a platelet-activating factor (PAF) receptor antagonist on hyperacute xenograft rejection; evaluation in a pig kidney–human blood xenoperfusion model - Cruzado, J M (Blackwell Publishing Ltd, 1998)
In pig to human discordant xenotransplantation, PAF may contribute to the pathogenesis of hyperacute xenograft rejection (HXR). We examined the release of PAF and the effect of a PAF receptor antagonist (BN 52021) on HXR in a pig kidney–human blood xenoperfusion model. Pig kidneys were perfused with porcine blood (AUTO group, n = 5), human blood (HETER group, n = 6) or human blood plus BN 52021 (BN group, n = 4), respectively. In contrast to HETER kidneys that never produced urine and were rejected in 15–30 min, the administration of BN 52021 induced a partial recovery of glomerular filtration rate and allowed kidneys to function until the end of the study. The release of PAF and soluble P-selectin, as well as endothelial P-selectin expression and tissue myeloperoxidase (MPO), were much higher in the HETER than in the AUTO group. HETER and BN kidneys displayed similar natural xenoantibody titres, CH(50), PAF, soluble P-selectin as well as renal immunoglobulin (IgM, IgG, IgA) and complement (C3, C1q) deposition. However, HETER kidneys displayed a full histologic picture of HXR (mainly interstitial haemorrhage and vascular microthrombi) and BN kidneys had only endothelial cell swelling. Also, BN 52021 administration attenuated glomerular and vascular P-selectin expression and renal tissue MPO activity. We conclude that in the pig kidney–human blood xenoperfusion model, PAF is produced in higher amounts than in the pig kidney–pig blood autologous combination. The administration of BN 52021 exerts a protective effect by means of attenuating the acute inflammatory response and blocking vascular microthrombi formation.